Could existing infrastructure for using patient‐reported outcomes as quality measures also be used for individual care in patients with colorectal cancer? - Clara Breidenbach; Christoph Kowalski; Simone Wesselmann; Nora Tabea Sibert (BMC, 2021)
Abstract Background There has been increasing interest in integrating patient-reported outcomes (PROs) into routine oncological practice. To date, however, PROs have rarely been implemented in Germany. Currently, PROs are being used as performance measures in colorectal cancer centers in Germany. This content analysis identified factors that may inhibit or facilitate the additional use of PROMs for individual patient management. Methods The analysis follows an exploratory approach. Out of 103 centers that participated in a multicentric PRO quality management and benchmarking program in Germany, twelve oncological health-care providers from eight certified colorectal cancer centers were interviewed using a semi-structured interview guide. The interviewees were clinicians (physicians, nurses, psycho-oncologist and physician assistant) who care for colorectal cancer patients. This analysis evaluated whether and how PROs that are primarily collected for quality management/benchmarking reasons could also be used for the management of individual patients. The data was analyzed using a content-analysis approach. Results The interviewees were not using PRO in their routine clinical work, but they recognized its added value and pointed out potential example uses. Identified inhibiting factors for the use of PROs in clinical routine work were effortful access to PRO reports, lacking coordinating structures, time delays and time points of measurements as well as redundancy with other instruments. Facilitating factors for the use of PROs in clinical routine work that were identified included access via electronic patient records, implementation of coordinating structures for PRO processes in the center, clear PRO reports that are easy to interpret, and measurements at relevant time points. Discussion Clinicians had quite a positive attitude toward PROs and recognized their added value. Inhibiting and facilitating factors of an organizational and technical nature were identified. Conclusions These findings indicate how PROs used for quality management purposes may also be used for the management of individual patients. Therefore, existing structures and processes in the certified colorectal cancer centers, as well as lessons learned from the literature on the implementation of PROs monitoring individual patients need to be taken into account.